Impact of land use and illegal human activities on the spatio-temporal distribution of Loxodonta africana (Cuvier, 1825) during the dry season in Arly National Park in Burkina Faso - Sawadogo, Emmanuel; Sandwidi, Harouna; Hema, Emmanuel M. (Frontiers in Environmental Science, 2023)
This study aimed to determine the impact of land use and illegal activities on elephant distributions in 2003, 2015 and 2021. Geospatial data inclusion satellite images of different characteristicsiques were was used as well as aerial count of animals along linear transects of varying widths. Using ArcMap 10.8, we laid grilles of 100 km2 covers covering the entire study area. We performed clipping to display and estimate the area of elephant's occupancy in each grid. As such, we were able determineto determine d the number of elephants and the number of illegal activities in each grid. Correlation analysis were performed to understand relationships between elephants' number and land-use units as well as illegalthe illega l activities. The identified different land use units were: rainfed crop, gallery forest, Wooded savanna, shrubby savanna, grass savanna, and water surface. Of the variables studied, only annual crop, gallery forest, shrubby savanna and illegal activities were significantly correlated with elephant numbers. Annual crop and illegal activities were negatively correlated with elephant numbers whilenumbers, while gallery forest and shrubby savanna were positive ly correlated with elephant abundance. These results confirmed that water, forage and quietnesserenitys are the main factors that explain the distribution of elephant in protected areas.